Demographic correlates of motivations for infidelity of men in romantic relationships - Đorđević, Tamara S. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2023)
Basic goal of this research was to examine demographic correlates of motivation for infidelity. It was conducted on a convenient sample consisting of 110 male participants. Participants were tested online and they were categorized by different age groups. The data used was based on gender, age, length of intimate relationships, marital status and religion. In order to establish the extent of infidelity The scale for examining motives of infidelity in love relationships (Stojkić, Solaković, 2017) were used. The results have shown that there are significant differences between men of different generations in terms of infidelity. Also, there is significant correlation between infidelity and lenght of intimate relationship, age and religion. On the other hand there is no correlation between motivation for infidelity and marital status.